Content Analysis on Cultural Context of Junior High School English Textbook - Lembah, Sri Ulfa Dwi Yana; Jusuf, Harni; Ismail, Abdul Kadir (Institut Agama Islam Negeri (IAIN) Manado, 2023)
Textbooks have important roles in learning, including learning English. English textbooksare not only a source of information about the material studied but also provide anoverview of the culture contained in the textbook. Concerning to culture, this researchaims to determine the culture portrayed in the English textbook